Scanning electron microscopy of amoeboid microglial cells in the transient cavum septum pellucidum in pre- and postnatal rats. - Tseng, C Y (1983)
The cavum septum pellucidum in rats of different ages was studied by light and scanning electron microscopy. A reconstruction from serial paraffin sections showed that the cavum was a pyramidal shaped closed cavity which was bounded above by the corpus callosum and inferolaterally by the lateral septal nuclei. The first sign of the cavum formation was noted in the 20 days post conception rat where there was a loosening up of the neuropil beneath the corpus callosum deep to the longitudinal fissure. A variable number of amoeboid microglial cells, characterised by their abundant eosinophilic cytoplasm, was seen among the smaller immature cells in the wide interstitial spaces. A definitive cavity was formed in the 21 days post conception rat and it continued to grow until the fifth postnatal day when it gradually diminished in size to become slit-like by the fifteenth postnatal day. The scanning electron microscope showed that the wall of the cavum was composed of a feltwork of glial and nerve fibres. Two types of cells were present in the cavum: cells identified as glioblasts, and amoeboid microglial cells. The glioblasts were were characterised by having a smooth cell body with radiating long processes. The amoeboid microglial cells showed diverse forms of surface protrusions: blebs, filopodia and membrane ruffles similar to other tissue macrophages. They were either adherent to the walls of the cavum, clustered around the blood vessel which traversed the cavum, or floating freely in the lumen. It was suggested that the amoeboid microglial cells were probably derived from extravasated blood monocytes in response to the physical damage resulting from the formation of the cavum septum pellucidum in the developing brain.